The Truth and Reconciliation Commission in post-conflict Sierra Leone - Allain, Jean (University of Pretoria, 2006)
Prepared under the supervision of Dr. Jean Allain at the Department of Political Sciences, School of Humanities and Social Sciences, the American University in Cairo, Egypt